Doenças raras: um estudo sobre os processos relacionados às políticas de medicamentos do SUS - Lopes, Luis Henrique (2014)
The structure of pharmaceutical care in the Brazilian National Health System (SUS - Sistema Único de Saúde) has been considered in recent years a strategy to increase qualification and access to essential medicines. The aim of the present paper is to study the processes related to rare diseases and SUS s medicines policies. The study is predominantly exploratory and of qualitative nature. The methodological approach was the collection of secondary data at Web of Science, and primary data collected with the participation of eleven respondents sampled fromhealth professionals based on referral centers and patients with rare diseases. Main results of the study indicate: 1) Gaps in academic production related to public health policies for rare diseases 2) Need for development and improvement in health management and professional training of health managers. The conclusion is that the development of pharmaceutical services structure constitutes one of the major challenges that managers and professionals in the SUS face to assist patients with rare diseases, either because of the financial resources involved or the need for continuous improvement in search for new strategies for its management and new processes geared to high-cost medicines and rare diseases